A study on high‐temperature co‐gasification reactivity characteristics and kinetics analysis of Hami coal and its liquefaction residue. Issue 1 (1st December 2019) - Guo, Qinghua; Huang, Yuchen; Gong, Yan; Wei, Juntao; Yu, Guangsuo
ABSTRACT: In this study, the rapid pyrolysis chars of Hami bituminous coal and its liquefaction residue were prepared using a high‐frequency furnace. A thermogravimetric analyzer was used to investigate the gasification reactivity and determine the mixing ratio of coal and its liquefaction residue. In addition, a scanning electron microscope, a physisorption analyzer, and a laser raman spectrometer were used to characterize the physicochemical properties of samples. Furthermore, kinetics analysis using the isoconversional method was conducted. The results showed that the gasification reactivity was affected by gasification temperature, pore structure, and carbon structure. When the gasification temperature increased to 1300 °C, the gasification reactivity of the liquefaction residue char was close to that of coal char. From the gasification reactivity point of view, the liquefaction residue could be utilized as a raw material in entrained‐flow gasification. The mixing ratio of the raw coal to the liquefaction residue was preferably 2:1. The research on activation energy showed that the gasification process belonged to pore diffusion control in the range of temperatures investigated. Specifically, there was a synergistic effect between the coal char and the liquefaction residue char in co‐gasification, which was beneficial to the gasification reaction.